Quality of Water Sources, Sanitation, and Hygiene in Households with Stunted Children in Rural and Urban Areas in West Java: Kualitas Sumber Air, Sanitasi, dan Higiene pada Keluarga dengan Balita Stunting di Daerah Pedesaan dan Perkotaan di Jawa Barat - Vieta Annisa Nurhidayati; Hadi Riyadi (Amerta Nutrition, 2022)
Background: The quality of water sources, sanitation, and hygiene have long been associated with the incidence of stunting in a household. Various studies show that this is also influenced by differences in access to water, sanitation, and hygiene in rural and urban areas. Objectives: This study aims to determine the condition of the quality of water sources, sanitation, and hygiene in household with stunted children under five in rural and urban areas. Methods: The study was conducted in June 2022 using cross-sectional method to 96 household with stunted children under five that were selected by systematic random sampling in Cianjur District and Sukabumi City. Structured questionnaire was used to collect data. Descriptive analysis and bivariate analysis were conducted to determine the distribution of use of water sources, sanitation facilities, and hygiene practices in household with stunted children under five based on the categories of improved sanitation facilities and drinking-water sources by World Health Organization and its differences in rural and urban areas. Results: The sources of drinking and cooking water used by the household with stunted children under five have been entirely improved sources. Most of the households in both areas had defecation facilities used only by household members. There were significant differences in the type of fecal waste disposal in household with stunted children under five in rural and urban areas. Majority of households in rural area (70.0%) already used septic tank for fecal waste disposal while majority of households in urban area (65.2%) disposed their fecal waste to river/lake/sea. Mothers’ handwashing practice at critical time were all above 80%, but only 33.6% of the households had separate handwashing facility and only 50.0% of them provide soap for handwashing. Conclusions: Based on the results, it is known that household with stunted children in rural and urban areas have used proper drinking water sources and have good hygiene practices. However, fecal disposal facilities in urban areas with high prevalence of stunting need to be improved as an effort to reduce stunting prevalence.